Micrometric detail in palaeoscolecid worms from Late Ordovician sandstones of the Tafilalt Konservat-Lagerstätte, Morocco - Gutiérrez-Marco, J. C.; García-Bellido, Diego (Gondwana Research, 2014)
The late Ordovician Tafilalt Biota of Morocco is a recently discovered Konservat-Lagerstätte that provides abundant paropsonemid eldonioids – resembling those from the Cambrian Burgess Shale and Chengjiang biotas, or other paropsonemid occurrences from the Ordovician to Silurian of the US and Australia – large discoidal ?holdfasts, non-biomineralised cheloniellid arthropods, rare vermiform fossils and articulated skeletons of echinoderms and trilobites. Exceptional preservation of soft-bodied organisms occurs in medium- to coarse-grained sandstones, in a style reminiscent of the soft-bodied Ediacaran fossils of the White Sea Assemblage. Here, we describe the first articulated scleritomes of a large palaeoscolecid worm from Africa. In addition to the mineralised sclerites, the specimens also exhibit extensive soft-tissue preservation down to micron-scale, including fine detail of annuli with their plate, platelet and microplate arrangement on a reticulate cuticle. Compression fossils of the new species Gamascolex vanroyi are represented by external moulds with remains of phosphatised cuticular structure, secondarily weathered into strontian crandallite. Partial foregut fossilisation is seen in one specimen, and phosphatised digestive structures are also reported in three co-occurring trilobite genera at the Bou Nemrou locality. From a palaeogeographic point of view, these North African palaeoscolecids represent the highest palaeolatitudinal occurrence of this Palaeozoic group in Gondwana, being described for the first time in cold-water areas adjacent to the Late Ordovician South Pole. It also provides a palaeobiogeographic link to the original distribution of the genus Gamascolex in a central European Peri-Gondwanan terrane. Peer reviewed